Stabilitas Struktur Dan Sistem Sambungan Pada Platform Rumah Apung Dengan Bahan Expanded Polystyrene / Styrofoam - Henny Pratiwi Adi (Universitas Islam Sultan Agung Semarang, 2020)
Flooding due to rising sea levels is the most common problem in Semarang city, especially in coastal areas. This flood can be prevented or minimized its impact, one way is to build a floating house. This study aims to analyze the use of Expanded Polystyrene (EPS) or styrofoam as a floating home platform. The building that was designed was a building that functioned as a residential house with an area of 85 m2 using light steel material as a component of the upper structure, wood material as a sloof structure, floors and walls and styrofoam as a platform material. The analysis shows the total weight of the upper structure and platform structure (G) of 555,887.5 Newton with a safety factor of 1.2. The strength of the buoyant force (Fa) of the platform structure using Styrofoam is equal to 588,000 Newton. The connection system on the floating house platform is a bolt connection system, 3 cm in diameter with a length of 22 cm anchor totaling 4 bolts on each connection. The connection between the filling materials can use Styrofoam glue and then arranged and made one unit with the platform frame.Keywords : floating house, platform, styrofoam